Prevalence of Microscopic Calcium Oxalate crystalluria in Biochemically Normal Urine Samples - Kuntal Devesh Patel (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Calcium oxalate is the major cause of human kidney stones in all over the globe. These arecolorless, refractile, and envelope-shaped. Sometimes dumbbell-shaped or peanut-like forms are seen. Theyare soluble in dilute Acids. Consumption of some types of foods like tomatoes, spinach, cabbage, asparagus,etc. causes upsurge in its number. A large number are seen in ethylene glycol poisoning.Method : This present research was aimed at investigating the prevalence of calcium oxalate crystalluria inbiochemically normal urine samples came to Clinical pathology section of Central Diagnostic Laboratory,Dhiraj General Hospital for the period of two months from 1st December 2019 to 31st January 2020. Theurine samples were centrifuged at 3000 rpm for 15 min. The supernatant were decanted and the sedimentswere viewed under microscope using high power objective lens with 40x magnification. Total 400 urinesamples with normal urine protein and normal urine sugar were analyzed microscopically using an Olympusmicroscope 4000x. Results showed that calcium oxalate crystals had the prevalence rate of 13.26 %.Conclusion: The study showed that this much of prevalence of COC was associated with food intake andthe social life style.